The Effect of Temperature Differences on The Gonad Maturity Levels and Embryogenesis of Vaname Shrimp Broodstock (Litopenaeus vannamei) - sultan wiguna dinata (2022)
Vaname shrimp cultivation in Indonesia is currently the mainstay of the aquaculture sector, in the 2012 - 2018 period, the contribution of the export value of vaname shrimp to the export value of Indonesian fisheries averaged 36.27%. The production of cultivated shrimp nationally has increased rapidly in the last 5 years with an average annual increase of 10.38%. To increase the production of vaname shrimp, it is necessary to observe the factors that can accelerate the level of gonadal maturity and embryogenesis in vaname shrimp. One of the environmental factors that affect the level of gonadal maturity and embryogenesis is temperature, temperature affects the sinus glands to accelerate the development of gonadal maturity levels, temperature also affects the process of embryo development, at high temperatures the shrimp metabolism rate increases and embryo development occurs more quickly. This research is experimental by using a Completely Randomized Design (CRD). This study used four treatments, namely four temperature treatments, including 28°C, 30°C, 32°C, and 34°C. The results of the study were analyzed using ANOVA (Analysis of Variance) and continued with Duncan's Multiple Range Test. The results of this study indicate that temperature differences affect the level of gonadal maturity level (GML) and embryogenesis in the spawning process of vaname shrimp (Litopenaeus vannamei) broodstock (p<0.05). The treatment that had a major influence on the level of gonadal maturity level (GML) was the 34°C treatment with 8 days and the fastest embryogenesis treatment at 34°C with 387.3 minutes.